Circular economy and innovative business - Loizidou Α.; Argyri, P. (Open Schools Journal for Open Science, 2020)
Taking into consideration the financial and environmental conditions of our era, I want to combine the “Functional Goals” that every business has, such as the pursuit of profit, the increase of its production and the social responsibility, with the innovation, the sustainable development, the protection of the environment and the rules of the well-known “circular economy”. In these terms in this paper, I present the project of an innovative business called “No Recycling Decoration”, to transfer the message that young people can make responsible decisions for their future.